94 President Oral Presentation Pick: Grazing diverse combinations of tanniferous and non-tanniferous legumes: Implications for beef cattle performance and environmental impact. (30th November 2020) - Lagrange, Sebastian; Beauchemin, Karen; MacAdam, Jennifer; Villalba, Juan J
Abstract: We tested the effect of increasingly diverse combinations of tanniferous legumes (birdsfoot trefoil-BFT, sainfoin-SF) and alfalfa (ALF) on cattle performance, methane (CH4) emissions and nitrogen (N) balance. Pairs of heifers (401 ± 49.6 kg) grazed three spatial replications of 7 treatments (n = 3/treatment): monocultures (BFT, SF, ALF) and all possible 2- and 3-way choices among strips of these legumes in a completely randomized block design of two 15-d periods during 2 consecutive years. Average daily gains (ADG) of heifers grazing the tanniferous legumes (1.05 kg/d) were 40% greater (P < 0.10) than of heifers grazing ALF (0.74 kg/d) during the first year. Heifers grazing the 3-way choice had greater intakes (10.4 vs 7.8 kg/d; P = 0.064) and ADG (1.21 vs. 0.95 kg/d, P = 0.054) than those grazing monocultures, suggesting a nutritional synergism among legumes. The average CH4 emissions for legume monocultures vs. 2- and 3-way choices was 222 vs. 202 and 162 g/kg BW gain (P > 0.10), respectively. For heifers grazing SF and BFT compared with ALF, blood urea N was less (14.3 and 16.8 vs 20.8 mg/dL; P < 0.05) as were urinary N concentrations (3.7 and 3.5 vs 6.0 g/L; P < 0.05), but fecal N concentrations were greater (34.5 and 35.5 vs 30.5 g/kg, respectively; P < 0.05). Combining both tanniferous legumes (SF-BFT) led to the greatest declines in urinary N (2.24 g/L) and urea-N (1.71 g/L) concentration, suggesting that different types of tannins in different legume species result in associative effects that enhance N economy. In addition, heifers grazing 3-way choices partitioned less N into urine (40.7 vs 50.6%; P = 0.037) and retained more N (36.1 vs 25.2%, P = 0.046) than heifers grazing monocultures. In summary, combinations of tanniferous legumes with alfalfa improved animal performance and reduced environmental impacts relative to monocultures, resulting in a more sustainable approach to beef production in pasture-based finishing systems.